Prenatal care: a look at the quality - Mayenne Myrcea Quintino Pereira Valente; Naiana Queiroz de Freitas; Aline Cruz Esmeraldo Áfio; Carla Suellen Pires de Sousa; Danielle Rosa Evangelista; Escolástica Rejane Ferreira Moura (Universidade Federal do Ceará, 2013)
This study aimed to assess the quality of prenatal care according to the criteria established in the Prenatal and Birth Humanization Program. Cross-sectional, descriptive and exploratory study carried out with 75 pregnant women registered in Basic Health Units of a municipality in the metropolitan region of Fortaleza, Ceará, Brazil. Data were collected between March and May, 2011, through interviews during prenatal nursing consultations. One highlighted major obstacles to a good quality prenatal care: deficits in the request of second routine laboratory tests in prenatal care, significant number of pregnant women who were not tested for fetal presentation and a small number of pregnant women who did not have the updated vaccine schedule. However investment is necessary to encourage and qualify professionals to perform their practices with a better performance. These practices can be developed through educational and health actions in order to improve the quality of prenatal care.